Morbidity prevalence and health care-seeking behavior of BRAC member and non-member households households: evidences from Matlab. Bangladesh - Ahmed, Syed Masud; Chowdhury, Mushtaque; Bhuiya, Abbas (BRAC Research and Evaluation Division (RED), 2020)
Understanding the morbidity profile-and health care seeking behaviour of socioeconomic strata of the community is important for planning and delivery of appropriate health services, especially for the poor. This paper attempts to explore the effects of the BRA.C development interventions on changes in health care-seeking behaviour of the beneficiary households. It is hypothesized that BRAC 's economic and non-economic inputs (like preventive health and nutrition intervention) through it's comprehensive Rural Development Programme (RDP) will influence the health care-seeking behaviour of the participant households by reducing the proportion of those who currently go without treatment or seek spiritual healing or largely in-effective traditional medicine.